Impact of cochlear implantation on the subjective assessment of tinnitus - Azevedo, Sara (2023)
Goals: Tinnitus is a frequent and disabling symptom. It has a prevalence of 85% in patients’ candidates to cochlear implant (CI) placement. In sensorineural hearing loss, the cochlear damage involved may be a triggering factor for its appearance. The main goal of this study was to determine the impact of cochlear implant placement on tinnitus complaints. Material and Methods: Prospective study that included 35 patients with bilateral severe or profound sensorineural hearing loss with complaints of bilateral tinnitus submitted to unilateral cochlear implant placement between January and September of 2022. All patients answered preoperatively and 3 months after CI placement to the Tinnitus Handicap Inventory. The severity of tinnitus was also defined. Results: the preoperative total mean THI result was 40.2 ± 32.2 points. 3 months after surgery, there was a decrease in the average of the final result (12.06±23.5) and in all its subcategories. The difference in mean was statistically significant between pre and postoperative periods (p < 0.05); in 16 of the 35 patients there was a complete resolution of the tinnitus and only one had a worsening. Conclusions: our study showed an improvement in tinnitus in most patients with unilateral CI placement and a resolution in almost half of them.